Control of molecular structure in the generation of highly luminescent liquid crystalline perylenebisimide derivatives: synthesis, liquid crystalline and photophysical properties - Jancy, B.; Asha, S. K. (Journal of Physical Chemistry B, 2006)
We report here, for the first time, the role of the molecular design on the liquid crystalline and solid-state photoluminescent properties of soluble and thermally stable liquid crystalline perylenebisimide derivatives. A new series of perylenebisimides were designed and developed for this purpose by adopting the stoichiometry-control approach, and amine-, hydroxyl-, ester-, and amide-functionalized molecules were synthesized. Various types of spacers with different lengths (C2 to C12), types (linear, cyclohexyl, and tricyclodecane), and end-capped by phenyl or tridodecyloxy gallic units were introduced in the perylenebisimide core. The molecules were completely characterized by NMR, FT-IR, SEC, and MALDI-TOF mass techniques. Thermal analysis revealed that the perylenebisimide derivatives were thermotropic liquid crystalline, and threadlike nematic phases were observed under a polarizing light microscope. The spacer length and the rigidity of the spacers play a major role in the liquid crystalline properties of the materials. In phenyl systems, the C6 chain with ester- and the C12 chain with amide-end-capped molecules showed a nematic phase, whereas the C6 chain with an amide end cap and their cyclic and tricyclic counterparts did not show any LC property. The introduction of a tridodecyloxy gallic unit induced the LC property in C12 and the cyclohexyl system; however, it failed to do so in the tricyclodecane molecule. The absorption properties of the molecules were almost unchanged by the structural variation; however, the emission quantum yield in solution and photoluminescent (PL) intensity in the solid state were significantly different. Though the gallic unit induced liquid crystallinity in the perylenebisimide core, the quantum yield and PL intensity are 4−5 times less compared to those of the simple phenyl-capped liquid crystalline system. Among the various types of spacers, the tricyclodecane induced strong molecular aggregates via π-stacking, which in turn increased the rigidity of the entire perylenebisimide core, resulting in the absence of liquid crystallinity and low luminescence compared to their linear and cyclohexyl analogues. The molecular aggregates were very stable even at very dilute concentration and also at high temperatures. The aggregates disappeared immediately upon addition of trifluoroacetic acid, thus confirming the strong hydrogen bonding in the aggregated states. In a nutshell, the present report demonstrates the importance of molecular design for introducing liquid crystalline phases in perylenebisimides and also the development of novel highly luminescent n-type π-conjugated material for application in optoelectronics.